Development of an Inclusive Campus Model Based in Universal Design for Learning in Supporting the Achievement of Students with Disabilities - Eva Meizara Puspita Dewi; Fattah Hanurawan; Nur Eva (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Higher education in Indonesia still faces challenges in building inclusive campuses for students with disabilities, particularly in physical-digital access, lecturer awareness, and support infrastructure. Therefore, an adaptive, inclusive, and equitable campus model is needed. This study aims to develop an inclusive campus model based on Universal Design for Learning (UDL) to improve the academic achievement of students with disabilities. The research method used is development research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research subjects consisted of 240 participants, including students with disabilities, managers of Disability Services Units, and the general public from various universities. Data were collected through literature studies, in-depth interviews, observations, and questionnaires, then analyzed using a qualitative descriptive approach and expert validation. The results of the study show that the implementation of the UDL-based inclusive campus model can improve academic accessibility, learning flexibility, and social support for students with disabilities. The implementation of this model in several universities has resulted in increased participation of students with disabilities in the learning process, increased understanding of lecturers regarding inclusive learning strategies, and improvements in campus infrastructure that is more disability-friendly. Evaluation of the model through expert testing and user feedback shows that this model is feasible to implement with some refinements to improve its effectiveness and sustainability. Thus, the UDL-based inclusive campus model can be an effective strategy for realizing inclusive, equitable, and diversity-oriented higher education.